True West : authenticity and the American West - Handley, William R.; Lewis, Nathaniel, 1962- (Postwestern horizons., 2004)
In no other region of the United States has the notion of authenticity played such an important yet elusive role as it has in the West. Though pervasive in literature, popular culture, and history, assumptions about western authenticity have not received adequate critical attention. Given the ongoing economic and social transformations in this vast region, the persistent nostalgia and desire for the "real" authentic West suggest regional and national identities at odds with themselves. True West explores the concept of authenticity as it is used to invent, test, advertise, and read the West. The fifteen essays collected here apply contemporary critical and cultural theory to western literary history, Native American literature and identities, the visual West, and the imagining of place. Ranging geographically from the Canadian Prairies to Buena Park's Entertainment Corridor in Southern California, and chronologically from early tourist narratives to contemporary environmental writing, True West challenges many assumptions we make about western writing and opens the door to an important new chapter in western literary history and cultural criticism.